IMPLEMENTATION OF SIMPELDESA AS AN EFFORT TO REALIZE A DIGITAL VILLAGE IN TAMBAK KALISOGO VILLAGE - Rachma Aulia, Sylvi; Fitria Agustina, Isna (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the implementation of the Simpeldesa application as a strategic step in realizing a digital village in Tambak Kalisogo Village, Sidoarjo Regency. The focus of this study is to evaluate the extent to which the implementation of village digitization policies through Simpeldesa can improve public services, village management efficiency, and community participation. Method: This study uses a qualitative approach with a case study method. Data collection techniques include in-depth interviews with village officials, direct observation of application use, and documentation related to policies. Data analysis was conducted using George C. Edwards III's implementation theory, which covers aspects of communication, resources, disposition, and bureaucratic structure. Results: The results of the study show that the implementation of Simpeldesa is still in the early adaptive stage. Thus, several obstacles were found in the aspects of resources and digital infrastructure readiness. The disposition of the implementing actors who support an adaptive bureaucratic structure is a major factor in the success of the program. Novelty: The novelty of this study lies in its focus on exploring implementation through the three pillars of smart villages to determine the focus of the Simpeldesa application in Tambak Kalisogo Village. This approach not only aims to understand the implementation of applications in supporting social networking and digital economic activities, but also to measure their impact on the lives of the people of Tambak Kalisogo Village.